Purposes and choices on the characterization of fossil samples: parameter test and analytical techniques applied to the comparison of different substrates - Silva, Natália Cantuária da (2022)
Historically, paleontology has been concerned with observational and explanatory issues regarding fossils. However, with the advancement of science and technology, a new field has been structured within this area: paleometry. This interdisciplinary effort seeks to understand how we can use a bulk of techniques in order to access information and interpret data on fossil record. The understanding of limitations and complementarities among techniques can clarify purposes and choices in paleontological research. Despite its contribution, paleometry as a science still needs to be further developed in technical terms. Here, we analyze sediments (sand and clay), rocks (siltstone and sandstone) and fossils (plants and insects) to compare and correlate patterns presented during the use of techniques that can facilitate the researcher's work, such as the use of high tensions related to the use of coating that allows us to see the sample in greater depth during the use of the Scanning Electron Microscope (SEM), as well as observations that the gradual increase in tensions is related to a greater detection of elements in the Spectroscopy of Dispersive Energy (EDS) and its correlation with trace elements found in X-Ray Fluorescence (XRF).